Pola Komunikasi Organisasi Antara Pimpinan Dan Karyawan Di Biro Perencanaan Kementerian Perdagangan - Margareth Mewita Dela; Panji Suratriadi; M. Ismail Alif (Tamilis Synex: Multidimensional Collaboration, 2024)
This study aims to identify and analyze the organizational communication patterns between leaders and employees in the Planning Bureau of the Ministry of Trade of the Republic of Indonesia. The communication patterns identified include the Wheel Pattern, Y Pattern, Chain Pattern, and All-Channel Pattern. This research employs a descriptive qualitative method with observation and interviews as data collection techniques. The data obtained were then analyzed using data reduction, data presentation, and conclusion drawing techniques to obtain a clear picture of the communication patterns implemented in the organization. The results show that organizational communication in the Planning Bureau of the Ministry of Trade is effective with the application of various communication patterns. The Wheel Pattern is used to channel information from the leader to the team leader, who then conveys it to the staff. The Y Pattern shows a clear communication hierarchy, while the Chain Pattern represents horizontal communication that allows information dissemination among individuals in equivalent positions. The All-Channel Pattern is used to maintain communication synergy among all elements within the organization, both formally and informally. However, there are several obstacles in the application of these communication patterns that may reduce the optimal flow of information and employee motivation. Therefore, increasing the effectiveness of communication within the organization is necessary to support the welfare and productivity of the company.